Effects of Amylose/Amylopectin Ratio and Baking Conditions on Resistant Starch Formation and Glycaemic Indices - Åkerberg, A.; Liljeberg, H.; Björck, I. (Journal of cereal science, 1998)
The possible improvement of the nutritional properties of starch in barley flour-based bread by using barley genotypes varying in amylose content (3–44%) was evaluated. Breads were made from 70% whole-meal barley flour and 30% white wheat flour. Test breads were baked from waxy barley (WB), ordinary barley (OB), ordinary Glacier barley (OGB) and high-amylose barley (HAB). Each bread was baked either at conventional baking conditions (45 min, 200 °C) or at pumpernickel conditions (20 h, 120 °C). A white wheat bread (WWB) was used as reference. The resistant starch (RS) content and rate of starch hydrolysis were measuredin vitro. The glycaemic index (GI) and the insulinaemic index (II) of the high-amylose breads were determined in healthy subjects. The amount of RS (total starch basis) varied from <1% (WB) to approximately 4% (HAB) in conventionally baked bread, and from about 2% to 10% in the corresponding long-time/low-temperature baked products. The long-time/low-temperature baked HAB displayed a significantly lower rate of starch hydrolysisin vitrocompared with WWB and reduced the incremental blood-glucose response in healthy subjects (GI=71). In contrast, the GI of the conventionally baked HAB was similar to that for WWB. It is concluded that a barley flour-based bread of low GI and high RS content can be obtained by choosing high-amylose barley and appropriate baking conditions.